Biochar Production, and Use: A Detailed Review of the Art (2024)
This study presents a detailed description of the technologies and processes for obtaining biochar and its formation from the fundamental structures of aromatic groups. These aromatic groups come from biomass pyrolysis; therefore, this document explores the complex relationship between biochar structural characteristics and the reactions involved in its formation during the pyrolysis process, specifically: analysis of the generation of a cross-linked network, structural features, and the impact of free radicals on biochar formation. This study will culminate with an analysis of microwave absorption and heat transfer dynamics among microwave absorbing materials and biomass or plastic particles. This examination aims to understand the temperature profiles in various heating modes, providing insights into their impacts on the overall performance of microwave-assisted reactors dedicated to these processes. Through this narrative, this study intends to provide an understanding of the multifaceted world of biochar and its diverse applications, drawing meaningful connections between its formation, structural attributes, and practical implementations.